The Implementation of the Preview, Question, Read, Summarize, and Test (PQRST) Learning Model to Improve the Learning Outcomes of Indonesian Language Content for Fifth-Grade Students at UPT SDN 123, Pinrang Regency - Musfirah, Musfirah; Yulia, Yulia; Sitti Hajrah; Imron Burhan (Cita konsultindo, 2025)
The main issue in this study is the low quality of the learning process and outcomes of fifth-grade students. This research aims to analyze the improvement in the learning process and student outcomes through the implementation of the Preview, Question, Read, Summarize, and Test (PQRST) learning model. A qualitative approach was used with a Classroom Action Research (CAR) design. The research subjects consisted of one teacher and 19 fifth-grade students at UPT SDN 123, Pinrang Regency, during the 2023/2024 academic year, comprising 12 male and 7 female students. This study focused on the learning process and student outcomes in fictional story material using the PQRST model. Data were collected through observation, tests, and documentation and analyzed qualitatively. In Cycle I, teacher and student observations were categorized as C. In Cycle II, teacher and student observations improved to category B. In conclusion, the implementation of the PQRST model can enhance both the learning process and student outcomes in reading fictional stories. Keywords: PQRST Model, Learning Outcomes, Reading Comprehension of Fictional Stories.